Low level laser therapy and rheumatoid arthritis: a systematic review and meta-analysis study - Amirali Salajegheh; Fatemeh Yazdi Yahyaabadi; Farzaneh Yazdi (PAGEPress Publications, 2024)
This systematic review and meta-analysis aimed to evaluate the efficacy of Low-Level Laser Therapy (LLLT) in the treatment of Rheumatoid Arthritis (RA), focusing on its effects on pain relief, grip strength, and morning stiffness. A comprehensive search was conducted across PubMed, Scopus, and Web of Science, yielding 3,111 articles. After eliminating duplicates and screening titles and abstracts, 94 full-text articles were assessed, and 23 studies met the eligibility criteria for inclusion in the systematic review. Of these, 22 studies were included in the meta-analysis. Data were extracted and analyzed using a random-effects model, with pooled Mean Differences (MD) calculated for the primary outcomes. The meta-analysis revealed that LLLT did not significantly reduce pain compared to placebo (MD = 0.00, 95% CI [-0.09, 0.09], p = 0.97). However, LLLT significantly improved grip strength (MD = -12.38, 95% CI [-17.42, -7.34], p < 0.01) and reduced morning stiffness (MD = -0.84, 95% CI [-1.33, -0.36], p < 0.01), despite substantial heterogeneity in these outcomes. LLLT shows promise in improving grip strength and reducing morning stiffness in RA patients, though it does not significantly impact pain relief. These findings highlight the potential role of LLLT as an adjunctive treatment for RA, with further research needed to optimize treatment protocols and clarify underlying mechanisms.